Selecting interventions to promote fruit and vegetable consumption: from policy to action, a planning framework case study in Western Australia - Pollard, Christina; Lewis, J.; Binns, Colin (Biomed Central, 2008)
Background: The Department of Health in Western Australia identified access to, and daily consumption of recommended amounts of fruit and vegetables, as priority health determinants. The numerous factors that influence supply and consumption of fruit and vegetables indicated that a comprehensive approach would be required. A government and non-government sector steering group was set up to select priority interventions using the National Public Health Partnership's Framework for Implementing Public Health Strategies. This structured framework was used for developing strategies to improve fruit and vegetable consumption and supply, and to identify implementation priorities. After one year a desktop audit of progress on framework interventions was undertaken.Results: The structured framework led to a plan for defined actions, partners, costs, and performance indicators for strategies to improve fruit and vegetable consumption and supply. Lead agency custodians for management of the selected interventions were identified. After one year there was significant progress in the implementation of a number of the high-ranking interventions. The exception was interventions that provide the infrastructure support such as research and development capacity, information systems. Conclusion: A structured framework and stakeholder participation assisted in developing a fruit and vegetable implementation strategy. Engagement and commitment of influential and diverse stakeholders is needed, not just for program support, but particularly in the areas of food and nutrition policy development and providing the infrastructure support required. Further work is required to develop performance outcomes and cost effectiveness measures for many of the strategies that have been proposed to address portfolio objectives.